2021
DOI: 10.1111/iej.13477
|View full text |Cite
|
Sign up to set email alerts
|

PRIASE 2021 guidelines for reporting animal studies in Endodontology: a consensus‐based development

Abstract: Animal testing is crucial in situations when research on humans is not allowed because of unknown health risks and ethical concerns. The current project aims to develop reporting guidelines exclusively for animal studies in Endodontology, using an established consensus‐based methodology. The guidelines have been named: Preferred Reporting Items for Animal Studies in Endodontology (PRIASE) 2021. Nine individuals (PD, VN, AK, PM, MN, JF, EP, JJ and SJ), including the project leaders (PD, VN) formed a steering co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 25 publications
(52 reference statements)
0
76
0
Order By: Relevance
“…This animal study was reported according to the PRIASE 2021 Guidelines (Fig. 1; Nagendrababu et al 2021). The general health condition of the rats remained constant throughout the experimental period.…”
Section: Resultsmentioning
confidence: 99%
“…This animal study was reported according to the PRIASE 2021 Guidelines (Fig. 1; Nagendrababu et al 2021). The general health condition of the rats remained constant throughout the experimental period.…”
Section: Resultsmentioning
confidence: 99%
“…The following sentence should be included in manuscripts when reports of animal studies followed the PRIASE 2021 guidelines: ‘This animal study was reported according to the PRIASE 2021 Guidelines (Nagendrababu et al . 2021)’. The adoption and endorsement of the PRIASE 2021 guidelines by relevant journals in their ‘Author guidelines’ will ensure the guidelines are used.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated these guidelines will be of value to researchers, editors and peer reviewers of scientific journals (Nagendrababu et al . 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations